3-Methyl-5-methylsulfanyl-1,3,4-thiadiazole-2(3H)-thione - Suarez, S.A. (2012)
The title compound, C4H6N2S3, has two very similar molecules per asymmetric unit. The nine non-H atoms in each molecule are coplanar, both having comparable r.m.s. deviations of 0.002 Å. The main interest in the rather simple structure resides in a survey of very weak (in some cases, borderline) non-bonding interactions of various kinds, viz. S···S, C - H·π, π-π [centroid-centroid distance = 3.8958 (13) Å] and C - S- ···π [3.7271 (11) Å], which act as the major driving force for the arrangement of molecules in the structure. The role of long, though highly directional, S···S contacts (d > 3.60 Å), and their relevance to the stability of the structure is discussed.